"'The scientific method' doesn't leave you". Issue 1 (3rd February 2021) - Harkness, Timandra
Abstract : Timandra Harkness interviews Trevor Phillips, the former head of the UK's Commission for Racial Equality and the Equality and Human Rights Commission, about Covid‐19 disparities, ethnic identities and origins, and the often fraught relationship between science and politics Abstract : Timandra Harkness interviews Trevor Phillips, the former head of the UK's Commission for Racial Equality and the Equality and Human Rights Commission, about Covid‐19 disparities, ethnic identities and origins, and the often fraught relationship between science and politics.